Exploring Students’ Experiences in Learning English Vocabulary through Taylor Swift’s “All Too Well (10 Minute Version)”: A Narrative Study - Zahrotul Khafida (Publikasi Inspirasi Indonesia, 2026)
This study investigates university students’ experiences in learning English vocabulary through Taylor Swift’s All Too Well (10 Minute Version). Unlike prior studies that predominantly employed quantitative methods or analyzed songs broadly, this research addresses a gap by deeply exploring how popular songs with strong narrative and emotional qualities foster meaningful vocabulary comprehension in English as a Foreign Language (EFL) contexts. Employing a qualitative narrative inquiry approach, data were collected through semi-structured interviews with two purposively selected students from the English Education Program at a university in Pekalongan City, chosen for their engagement with the song. Findings reveal that the song’s narrative structure significantly enhances contextual learning, enabling participants to infer and retain complex vocabulary. Furthermore, the emotional depth of the lyrics cultivates intrinsic motivation and engagement, transforming vocabulary acquisition into a more meaningful process. Participants also demonstrated active vocabulary application by integrating new words into authentic contexts, such as daily journaling. These findings underscore the potential of narrative-driven popular music as an effective and engaging tool for EFL vocabulary acquisition.